Influence of theoretical approaches of public administration in sports on the formation of the modern sports policy in Ukraine - S Lishchuk (Kazimierz Wielki University, 2014)
Lishchuk S. Influence of theoretical approaches of public administration in sports on the formation of the modern sports policy in Ukraine. Journal of Education, Health and Sport. 2015;5(2):281-288. ISSN 2391-8306. DOI: 10.5281/zenodo.17834 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A281-288 https://pbn.nauka.gov.pl/works/561263 http://dx.doi.org/10.5281/zenodo.17834 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015.   INFLUENCE OF THEORETICAL APPROACHES OF PUBLIC ADMINISTRATION IN SPORTS ON THE FORMATION OF THE MODERN SPORTS POLICY IN UKRAINE S. Lishchuk National University of Water Management and Nature Resources Use     Summary. The article investigates the influence of theoretical approaches of public administration in sports on the formation of the modern sports policy in Ukraine. Research two models of public administration in sport: liberal model (or "laissez-faire model"), that provides for maximum freedom of self-regulation by the state government and sports organizations and minimize government interference in the affairs of the sport; an interventionist model, which provides for the active intervention of the state in the affairs of sports activities and sports organizations. It proved that Ukraine has an interventionist model. Given the task to the Ministry of Youth and Sports of Ukraine, it should establish a working group at the Ministry of Youth and Sports of Ukraine on the implementation of the learning process of the course devoted to the legal foundations of physical culture and sports as law students and students of universities of physical education and sport. Moreover Syllabus should vary with account available, depending on the direction of training, basic knowledge in the field of physical culture and sports and jurisprudence; spend work to promote information on legal foundations of physical culture and sports use to implement the media, organize conferences on legal issues in the field of physical culture and sports, pay attention to the development of textbooks on the subject, etc; create a system of training of lawyers with specialization in the field of physical culture and sports.   Keywords: Physical Education and Sports, the mechanisms of state regulation of physical culture and sports in Ukraine, public policy in the development of physical culture and sports.